ABI5 regulates ABA-induced anthocyanin biosynthesis by modulating the MYB1-bHLH3 complex in apple. (7th November 2020) - An, Jian-Ping; Zhang, Xiao-Wei; Liu, Ya-Jing; Wang, Xiao-Fei; You, Chun-Xiang; Hao, Yu-Jin
Abstract : The apple bZIP transcription factor MdABI5 positively regulates ABA-induced anthocyanin accumulation by activating the binding of MdbHLH3 to the promoters of anthocyanin biosynthesis genes, and by enhancing ABA-promoted MdMYB1-MdbHLH3 interaction. Abstract: Abscisic acid (ABA) induces anthocyanin biosynthesis in many plant species. However, the molecular mechanism of ABA-regulated anthocyanin biosynthesis remains unclear. As a crucial regulator of ABA signaling, ABSCISIC ACID-INSENSITIVE5 (ABI5) is involved in many aspects of plant growth and development, yet its regulation of anthocyanin biosynthesis has not been elucidated. In this study, we found that MdABI5, the apple homolog of Arabidopsis ABI5, positively regulated ABA-induced anthocyanin biosynthesis. A series of biochemical tests showed that MdABI5 specifically interacts with basic helix-loop-helix 3 (MdbHLH3), a positive regulator of anthocyanin biosynthesis. MdABI5 enhanced the binding of MdbHLH3 to its target genes dihydroflavonol 4-reductase ( MdDFR ) and UDP flavonoid glucosyl transferase ( MdUF3GT ). In addition, MdABI5 directly bound to the promoter of MdbHLH3 to activate its expression. Moreover, MdABI5 enhanced ABA-promoted interaction between MdMYB1 and MdbHLH3. Finally, antisense suppression of MdbHLH3 significantly reduced anthocyanin biosynthesis promoted by MdABI5, indicating that MdABI5-promoted anthocyanin biosynthesis was dependent on MdbHLH3. Taken together, our data suggest that MdABI5 plays a positive role in ABA-induced anthocyanin biosynthesis by modulating the MdbHLH3-MdMYB1 complex. Our work broadens the regulatory network of ABA-mediated anthocyanin biosynthesis, providing new insights to further study the transcriptional regulatory mechanisms behind this process.